Taqwa as The Primary Driver of Islamic Fintech Adoption Intention: Empirical Evidence from Muslim Students in Indonesia - Iwandi Iwandi; Jum Harroni; Muhammad Irwan Padli Nasution; Yusrizal Yusrizal; Muhammad Habibie Siregar (Sharia Economic and Management Business Journal (SEMBJ), 2026)
Background: This study examines the influence of spiritual values and religiosity on behavioral intention to use Islamic fintech, with trust in sharia governance as a mediating variable. Using a quantitative approach with Partial Least Squares Structural Equation Method: Modeling (PLS-SEM), data were collected from 1480 student respondents through questionnaires. The study analyzes relationships among Perceived Taqwa Value, Spiritual Risk Aversion, Religio-Financial Literacy, Religious Social Norms, Trust in Sharia Governance, and Behavioral Intention. Results: The findings reveal that Perceived Taqwa Value significantly and positively affects the intention to use Islamic fintech. However, Spiritual Risk Aversion, Religio-Financial Literacy, Religious Social Norms, and Trust in Sharia Governance do not show significant direct effects. Additionally, trust in sharia governance does not function as a mediating variable. The primary barriers identified are limited financial capacity and lack of experience with Islamic fintech services. Conclusion: This study contributes to the development of the Theory of Planned Behavior (TPB) by incorporating spiritual and religious dimensions in financial behavior analysis. It highlights that taqwa is a key driver in shaping sharia-based financial intentions among young Muslims. The study suggests that Islamic fintech providers should emphasize spiritual values and improve accessibility through affordable services. Future research should involve broader samples and consider economic factors.